Medicinal Plants of Asia and the Pacific - Wiart, Christophe (CRC/Taylor & Francis, 2006)
Covering various aspects of botany, ethnology, pharmacology, toxicology, pharmacy, and medicine, this volume presents important classes of natural products found in Asia and the Pacific, classified by their mode of action. It includes figures of plants, concepts, and mechanisms of action